Effects of Temperature and Channel Doping on the BSIM3 Threshold Voltage Model of NMOSFET form Substrate Bias Dependent Methodology - Muanghlua, Rangson; Niemcharoen, Surasak; Poyai, Amporn; Ruangphanit, Anucha (My University, 2016)
The effects of channel doping and temperature dependence on the BSIM3 threshold voltage model of NMOSFET form substrate bias dependent methodology is proposed. The IDS -VGS in linear region with different substrate bias condition of a big size of NMOSFET was used. The threshold voltage parameters extraction procedure is based on the measurement of the transconductance characteristics of MOSFET in linear region. The electrical parameters γ, NCH and NSUB also the BSIM3 model parameter K1 and K2 at different channel implanted dose and different operating temperature are extracted. The model can be implemented in simulation tools with the error is less than 5%.
Keywords: BSIM3; NMOSFET; Threshold voltage